PELAKSANAAN UNDANG- UNDANG NOMOR 8 TAHUN 1999 TERHADAP PENGGUNAAN KARTU PURNA JUAL - Putri Sarina, Ukas (Jurnal Cahaya Keadilan, 2017)
Human as zoon politicon where relationship human with same humananother constitute important thing for stationary fulfil, requirement eachespecially at tools wearing tool technological comprise trick and thatmedium exploit. Inside rights consumerism to get information andtechnology purpose constituted to do bit agents effort. For meeting of thatthing, there are five Section Minister decision about industries andcommerce. On duty perindusterian and commerce (ESDM) constitute acommanding institution that given by copetency to keep company and givestraining for effort agent (producer) that consumer rights rights as wearing asproduct gets certainty and imformasi and or service and absolute alaresponsibility as one is managed in UUPK. In this research its problemformulation is how UUPK'S performing relates post card purpose sell anddetention and solution in that UUPK'S performing its bearing with kepmenperindusterian and Perdagangann Ttg Is card purpose road map gransi'ssurety. This research utilize sosiologis's judicial formality approximatemethods, with type with direct data of society over and above materiallibrary, observing data collecting tool, interview and analisisi's approachingthat gets kualitatif's character. Simpulan of this research is that UUPK'Sperforming and kepmen No. 547 was walking, but haven't terlaksananmaximal ala, meanwhile interference and observation facet that needs to beincreased